Advances in Bioinformatics and Computational Biology 4th Brazilian Symposium on Bioinformatics, BSB 2009, Porto Alegre, Brazil, July 29-31, 2009. Proceedings - Guimarês, Katia S.; Panchenko, Anna.; Przytycka, Teresa M. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 4th Brazilian Symposium on Bioinformatics, BSB 2009, held in Porto Alegre, Brazil, in July 2009 The 12 revised full papers and 6 extended abstracts were carefully reviewed and selected from 55 submissions. The papers are organized in topical sections on algorithmic approaches for molecular biology problems; micro-array analysis; machine learning methods for classification; and in silico simulation.